Space science and the international traffic in arms regulations : summary of a workshop (National Research Council, 2008)
"ITAR, which controls defense trade, includes the U.S. Munitions List (USML) which specifies categories of defense articles and services covered by the regulations. In 1999, space satellites were added to the USML. In 2002 ITAR was amended to exclude U.S. universities from having to obtain ITAR licenses when performing fundamental research involving foreign countries and/or persons. Despite this provision, there remains considerable uncertainty among university researchers about whether the regulations apply to their research leading to a rather conservative interpretation of the regulations and the imposition of burdens that might not be necessary. To explore this concern, NASA asked the NRC to organize a workshop of all stakeholders on the implications of ITAR for space science. This book presents a summary of the workshop discussions including those on perspectives on recent developments and implementation of ITAR; overarching issues; problems arising from ITAR's implementation; and opportunities for near-term actions and improvements."--NAP web site